Identificação assistida por docking molecular de potenciais alvos em Plasmodium falciparum para derivados de indol-3-glioxiltirosina com atividade antimalárica in vitro - Dávila Rodríguez, María José (Universidade Federal de São Carlos, 2020)
Malaria, although it is no longer considered a neglected disease, remains a public health problem. In 2018 alone, the World Health Organization estimated 228 million new cases and 405,000 deaths worldwide. Currently, chemotherapy is the only strategy available for the treatment of this disease. However, the emergence of resistance from Plasmodium spp. to the available antimalarials makes it necessary and preeminent to develop new drugs to treat it. In this sense, the in vitro activity against Plasmodium falciparum, in the intraerythrocytic stage, of a series of indole-3-glyoxyl tyrosine derivatives are described in the literature. As in recent years, computer-aided methods for drug development have made great advances, being commonly integrated into the preclinical development phase, their use was applied to try to unveil their mechanism of action and/or target which is unknown. In this work, we employ inverse virtual screening based on molecular docking to identify potential targets for the indole-3-glyoxyl tyrosine derivatives. In total, 34 different enzymes from Plasmodium falciparum, with structures available in the Protein Data Bank, were evaluated in detail using molecular docking simulations. Besides, molecular dynamics simulations were used to study the stability of the protein-ligand complexes considered to be promising leads. The results indicated the enzymes dihydroorotate dehydrogenase (DHODH) and plasmepsin II (PMII), of Plasmodium falciparum, as potential targets. The docking simulations showed that the most active compounds would be able to establish the key non-covalent interactions needed for target inhibition, that is, the docking results agree with the experimental values of the antiparasitic activity. Molecular dynamics was used to study the stability of protein-ligand complexes in a situation that simulates biological conditions. All of these results show that the methodology described here can be used in the optimization of the indole-3-glyoxyl tyrosine derivatives aiming at increasing their antiplasmodial activity.
Identification, assisted by molecular docking, of potential targets in Plasmodium falciparum for indole-3-glyoxyl tyrosine derivatives with in vitro antimalarial activity
Keywords: Triagem virtual inversa; Malária; Indol-3-glioxiltirosina.; Docking; Inverse virtual screening; Indole-3-glyoxyl tyrosine; CIENCIAS EXATAS E DA TERRA::QUIMICA